2017
DOI: 10.1073/pnas.1621179114
|View full text |Cite
|
Sign up to set email alerts
|

The POTRA domains of Toc75 exhibit chaperone-like function to facilitate import into chloroplasts

Abstract: Protein trafficking across membranes is an essential function in cells; however, the exact mechanism for how this occurs is not well understood. In the endosymbionts, mitochondria and chloroplasts, the vast majority of proteins are synthesized in the cytoplasm as preproteins and then imported into the organelles via specialized machineries. In chloroplasts, protein import is accomplished by the TOC (translocon on the outer chloroplast membrane) and TIC (translocon on the inner chloroplast membrane) machineries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 79 publications
1
32
0
Order By: Relevance
“…The changes in dimerization could be sufficient to promote transit peptide insertion even in the absence of nucleotide exchange. It has also been shown that the intermembrane space-localized POTRA domains of Toc75 possess a transit peptide binding site (Paila et al, 2016;O'Neil et al, 2017), which could serve as a docking site for the transit peptide in the intermembrane space and reduce backsliding out of the channel in the absence of energy. In mitochondrial protein import, it has been shown that Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in dimerization could be sufficient to promote transit peptide insertion even in the absence of nucleotide exchange. It has also been shown that the intermembrane space-localized POTRA domains of Toc75 possess a transit peptide binding site (Paila et al, 2016;O'Neil et al, 2017), which could serve as a docking site for the transit peptide in the intermembrane space and reduce backsliding out of the channel in the absence of energy. In mitochondrial protein import, it has been shown that Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…The receptors are associated with Toc75, a β-barrel outer membrane protein, which forms the channel through which preproteins are translocated across the outer membrane (Schnell et al, 1994;Hinnah et al, 2002;Day et al, 2014). Toc75 is also proposed to interact with preproteins in the intermembrane space via its POTRA (polypeptide-transport associated) domains (Chen et al, 2016;Paila et al, 2016;O'Neil et al, 2017), as the POTRAs bind to preproteins and possess molecular chaperone activity in vitro (O'Neil et al, 2017). In addition, the POTRAs interact with two putative chaperones in the intermembrane space, Tic22-III and Tic22-IV, leading to the hypothesis that the Toc75 POTRAs and Tic22 proteins function coordinately to facilitate transit of the preprotein across the intermembrane space (Paila et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…cpHsp70, Hsp90C) or a 2 MDa Ycf2-FtsHi complex. The Tic40 and Tic110 proteins are also involved in the import process, and may operate downstream in soluble N-terminal polypeptide transport-associated (POTRA) domain [52], which in the case of Toc75 extends into the intermembrane space (IMS) and performs a proposed chaperone-like role [53]. The Toc75 channel has been found to reach a maximum diameter of 30 Å [54].…”
Section: Part 1 Ofmentioning
confidence: 99%
“…The POTRA repeat containing domain of eukaryotic and prokaryotic Omp85 proteins was proven to bind to non‐native porins and to peptides mimicking nascent unfolded OMPs (Voulhoux et al , ; Bredemeier et al , ; Kim et al , ; Knowles et al , ). Recently, a chaperone or holdase‐like function has been proposed for the POTRA domains (O'Neil et al , ). Experimentally determined and modeled structures of BamA and BAM revealed the existence of an open and a closed BamA conformation.…”
Section: Introductionmentioning
confidence: 99%